Outplaying opponents—a differential perspective on passes using position data - Steiner, S.; Rauh, S.; Rumo, M.; Sonderegger, K.; Seiler, R. (German Journal of Exercise and Sport Research, 2019)
In recent years, the availability of new tracking technologies has enabled new perspectives on passes played in football. One such perspective includes measuring the number of opponents that are outplayed by a pass (NOO). Various studies substantiate that this measure qualifies as one aspect of the passes` offensive quality. Given the latent consensus that high-NOO passes indicate clever passing decisions, one aim of this study was to analyze how athletes prioritize contextually embedded passing options when playing passes that differ with regard to their NOO. Another aim was to determine the contributions of pass receivers to completing passes with different NOOs. To this end, position- and speed-related features of 12,411 passing options from 1,379 passing situations tracked during championship matches were analyzed. Overall, the findings indicate that decisions to play high NOO passes differ from decisions to play low NOO passes with regard to how contextually embedded passing options are prioritized. The passes` NOOs increased as the decision-makers` tendency to pass to loosely defended team members with open passing lanes and positions near the ball carrier decreased. Furthermore, higher physical contributions on the part of the pass receivers were observed when pass receivers completed passes with higher NOOs. Based on the findings, passes with a high NOO could be considered risky passes. The presented approach could be adopted to further analyze the circumstances that allow athletes to play such passes compared with those that absolutely do not, which could represent an important step concerning educational programs in football.